The linkage of competence, professionalism and islamic work ethic: A literature review - Nurfahmiyati Hasan Basri; Zainuddin Maliki; Sri Iswati; Rofi Rofaida; Harlina Meidiaswati (Journal of Innovation in Business and Economics, 2020)
This paper aims to encourage the relationship between competence, professionalism, and the concept of Islamic work ethics as a proxy. Through a literature review, the results of this study show that in general, the study of competence, professionalism, and the concept of Islamic work ethics can be divided into three major groups, namely conceptual or theoretical studies, empirical studies of the effect of Islamic work ethics on performance, and efforts to increase the role of Islamic work ethics. Based on the selected literature and supported by major references, it can be concluded that there is an agreement between the concept of competence and conventional professionalism with Islamic work ethic. However, this study also does not deny that the implementation of Islamic work ethics still faces several obstacles and needs to continue to find solutions.